Gambaran Kebiasaan Sarapan Pagi dan Kejadian Gizi Kurang pada Remaja Putridi SMP N 2 Kota Jambi - Rahmatia, Nurlaila; Indrawati, Iin; Aisah, Aisah; Gustra Jeki, Andicha (3031-8572, 2024)
One of the causes of nutritional problems in adolescents can be caused by breakfast habits. A good breakfast pattern will affect the child's nutrition. Breakfast is a human need that should be done regularly every morning, for nutritional needs and brain development and to avoid the risk of malnutrition and obesity. WHO 2016 with the category of undernourished girls 8.4% and boys 12.4, Riskesdas 2018 prevalence of nutritional status of adolescents 13-15 years very thin 2.1% and thin 5.5%. The Jambi City Health Office in 2022, the working area of Koni Community Health Centre at the junior high school level with 444 cases experiencing malnutrition, the aim of this study was to describe the breakfast habits and the incidence of malnutrition in adolescent girls at SMP N 2 Jambi City. This type of research is descriptive research, data collection by distributing questionnaires and measuring nutritional status. The sample size was 58 adolescents. Data analysis was done using univariate analysis. The results showed that the percentage of breakfast habits of adolescent girls at SMPN 2 Jambi City with good habits was 56.9% and not good as much as 43.1%. The description of the incidence of malnutrition with malnutrition status as much as (31%) and not malnutrition as much as (69%). It can be concluded that most adolescent girls already have good breakfast habits and most have a nutritional status that is not malnourished. For those adolescents who still have bad breakfast habits, it is recommended that they get used to it, as it can have an impact on the health level of these adolescents.